"Through the digits, through the fingers": Variations on the string figure as imaginary digital medium. (April 2023) - Svec, Henry Adam
This article considers artistic engagements with string figure performance and collection as 'imaginary' articulations of digital media. As an object of anthropological inquiry, the string figure emerges in 1888 with a short paper by Franz Boas. Encouraged by more mainstream publications by Caroline Furness Jansen (2008) and Kathleen Haddon (1930), over the course of the 20th century the string figure would become a model through which largely western writers and artists have explored both the anxieties and dreams of ideal, embodied and networked communication technologies. The present article explores, specifically, the collecting projects and films of Harry Smith in the 1960s and 1970s; the video-performance piece of 1974, titled String Games: Improvisations for Inter-City Video, by the interdisciplinary artist Vera Frenkel; and the string figure exhibit at David Wilson's Museum of Jurassic Technology in Culver City, California. Through a media-archeological lens, the history of string figure fascination takes shape as a repository of dreams about (digital) communication, which, it is additionally suggested in a final section, might yet allow for the expansion and enlargement of conceptions of both digitality and media.